Geriatric Endodontic - Singh, Santosh Kumar; Kanaparthy, Aruna; Kanaparthy, Rosaiah; Pillai, Ajay; Sandhu, Garima (Journal of Orofacial Research, 2013)
Developments in medicine have resulted in an increase in the life span of people, thereby leading to an increase in the number of geriatric patients. Adverse oral health has been identified as a risk factor for several systemic disorders/diseases. Therefore, dental care should be integrated into overall health management of all geriatric patients. Increased numbers of such patients in dentistry has resulted in the preferred use of alternatives like endodontics rather than extractions to improve the longevity of the natural dentition. Special knowledge, skills and attitude are necessary for the management of the geriatric patients. This review discusses the unique challenges faced by the endodontist in carrying out root canal treatment in such individuals.